(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Socio-psychological and constructional approaches to the examinationthe of essence and structure of conflict competence of a specialist have been worked out and theoretically substantiated in the article. The model of conflict competence of futteacherscher has been presented and the criteria of its development have been marked out.